Does exposure to bullying behaviors at the workplace contribute to later suicidal ideation? A three-wave longitudinal study - Morten Birkeland Nielsen; Ståle Einarsen; Guy Notelaers; Geir Høstmark Nielsen (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVE: This study aimed to determine the relative impact of person-related, work-related and physically intimidating bullying behaviors on suicidal ideation two and five years after the fact. METHODS: Logistic regression analyses were utilized to examine relationships between bullying behaviors and suicidal ideation in a random and representative cohort sample of 1775 (T1-T2)/1613 (T1-T3) Norwegian employees. The time lag between T1 and T2 was two years and five years between T1 and T3. Exposure to bullying behaviors was measured with the revised version of the Negative Acts Questionnaire. Suicidal ideation was measured with a single item asking respondents whether they had "Thoughts about ending your life" during the past seven days. RESULTS: Prevalence of suicidal ideation was 4% at T1, 5% at T2, and 4.2% at T3. At T1, 8.2% reported monthly exposure to person-related bullying, 19.1% to work-related bullying, and 1.8% to physically intimidating bullying behaviors. After adjusting for demographic characteristics, baseline suicidal ideation, and the shared variance of the bullying behavior categories, exposure to physical intimidation was the only form of bullying which significantly predicted suicidal ideation two [odds ratio (OR) 10.68, 95% confidence interval (95% CI) 4.13-27.58) and five (OR 6.41, 95% CI 1.85-22.14) years later. CONCLUSIONS: Exposure to workplace bullying behaviors in the form of physically intimidating behaviors is a risk factor for suicidal ideation. Although the prevalence of physical intimidation is low, this study shows that the consequences can be detrimental and organizations should therefore be especially aware of, and have available measures against, this type of bullying.